Penentuan Sudut Kemiringan Optimal Panel Surya Untuk Wilayah Meulaboh - Ali, Syukarni; AzisPandria, T M (universitas teuku umar, 2018)
Development of energy especially alternative energy and renewables continue to be encouraged, one of which is becoming the trend of the world today is focused towards the development of solar energy. The optimum angle of tilt of the photovoltaic panel is one of the deciding factor against the acceptance of the amount of solar radiation in the amount of the maximum, so that will affect the power output of a photovoltaic panel. Method of calculation of the Altitude angle is a way to find out the optimum height of the positions of the Sun, and these factors influence the position of the slope of the surface of the panel sector in the region, so by knowing the position of the right angle of the Sun will be able to obtain the maximum amount of radiation against photovoltaic panels. Adjustment of the angle of the slope against the monthly solar panels in the region of Meulaboh is affected by the angle of altitude. January and March, the optimum angle value starts from 35,54 ? to 12,39 ? . April does not occur, because of the angle position of the panel surface horizontal is same. May to December, the orientation of the panel turned south-facing surface of the panel with face down which is characterized by a negative notation.Keywords ? the photovoltaic panels, the altitude angles, optimal angle, orientation